Effect of Cr addition on microstructure and oxidation resistance of a Ti5Si3-containing MoSiBTiC alloy. (15th April 2020) - Hatakeyama, Tomotaka; Sekido, Nobuaki; Yoshimi, Kyosuke
Highlights: The effect of Cr on the oxidation resistance of MoSiBTiC alloy is investigated. Substitution of 10 at. % Cr hardly changes the microstructure of the alloy. Cr addition significantly enhance the oxidation resistance of the alloy at 800 °C. Abstract: The effect of Cr addition on the oxidation behaviour of multiphase Mo–28Ti–14Si–6C–6B (at. %) alloy composed of Mo solid solution, Mo5 SiB2, Ti5 Si3, and TiC phases was investigated. Replacement of 10 at. % Cr for Mo hardly changed the microstructure of the alloy and significantly enhanced its oxidation resistance at 800 °C. At 1100 °C, the Cr-added MoSiBTiC alloy showed less weight loss than the Cr-free base alloy. However, Cr addition had little effect on the substrate reduction, particularly for longer oxidation periods, due to the high volatility of Cr oxide at higher temperatures.